Predicting the frost heaving of bottom ash value for road design - A. A. Lunev; D. A. Razuvaev; V. V. Golubenko; M. G. Chakhlov (Вестник СибАДИ, 2020)
Introduction. Most of the researchers dealing with the use of ash and slag materials (especially in the construction) have focused on the study of their mechanical characteristics or assessment of their impact on the environment. At the same time, the design of roads with embankments of soil materials in the Northern regions requires taking into account the behavior of materials in cold climates.Although ash and slag materials are a typical dispersed soil, it is prone to frost heaving (due to the peculiarities of the internal structure). In addition, these materials have not been sufficiently tested in the development of the Russian Federation standards and codes for road design. Therefore, the professional environment is developing a hypothesis about the inadmissibility of using ash and slag materials in road embankments due to excessive frost heaving of this material, which, in our opinion, is not the case.Methods of research. To obtain real values of ash and slag frost heaving, specialists of Siberian State Transport University carried out additional studies to determine the relative deformations of frost heaving of medium-grained samples and coarse-grained ash slabs. SibADI specialists compared the results obtained with earlier studies to determine the relative deformations of frost heaving of fine-grained ash slabs samples, and analyzed the entire array of data obtained.Results. As a result of joint work, an empirical model was obtained that makes it possible to predict the amount of frost heaving of ash and slag material depending on its degree of compaction, initial moisture content (when working in a closed circuit or moisture in freezing through an open system), particle size distribution and freezing temperature. This makes it possible to determine the degree of frost heaving of ash and slag systems based on the grain size composition and the calculated characteristics of the subgrade.